Two Fast Retransmit Techniques in UWSNs with ACK Indiscretion Problem. (13th February 2014) - Lee, Sungwon; Kim, Dongkyun
In underwater wireless sensor networks (UWSNs), flooding-based routing protocols are preferred due to their capability of reducing the routing overhead in terms of no need of path setup and maintenance. In addition to routing, a transport protocol should be developed to recover lost DATA segments in loss-prone UWSNs. In particular, due to long propagation delay in UWSNS, a fast end-to-end recovery technique needs to be developed. Fortunately, the Fast Retransmit technique well-defined in TCP can be exploited for fast retransmissions of lost DATA segments. However, if it operates over the flooding-based routing protocols, each source node will receive multiple copies of ACK segments which are transmitted along different paths. Therefore, the source node cannot distinguish between these multiple copies of ACK segments and real duplicated ACK segments (defined as an ACK indiscretion problem in this paper), which leads to unnecessary retransmissions. In this paper, we therefore propose two Fast Retransmit techniques to address the ACK indiscretion problem. In our first proposed technique, the sink records a new count number into a header, informing how many duplicated ACK segments have been transmitted from the sink. Since this requires an additional field in the header for the count number, the second technique allows a source node to estimate the number of ACK copies which are expected to be received when the sink transmits an ACK segment, without any dependency on the additional field. From both of our proposed techniques, the source nodes become aware of the accurate number of duplicated ACK segments transmitted from the sink and can perform the Fast Retransmit correctly.